Techno‑Enviroeconomic Modeling of a Solar‑Green Hydrogen System with Industrial Wastewater Reuse via Integrated Hourly Simulation‑LCA‑DCF - Raja, Irtaza Bashir; Ahmad, Yasir; Feroze, Tariq; Genc, Bekir (New Energy Exploitation and Application, 2026)
Solar–hydrogen hybrid systems provide low-carbon and dispatchable energy, yet most existing configurations implicitly assume freshwater availability, thereby overlooking the role of water reuse in water-stressed regions. In semi-arid industrial contexts, the integration of clean energy systems with circular water management is essential for long-term sustainability. This study develops a closed-loop Solar–Green Hydrogen Hybrid System (SGHHS) in which industrial effluent is treated through a membrane bioreactor–reverse osmosis–deionization (MBR→RO→DI) sequence to satisfy proton exchange membrane (PEM) electrolyzer water-quality requirements, while water recovered from fuel-cell exhaust is captured as condensate, achieving an overall water recovery rate of approximately 90%. The proposed system consists of a 22.75 MW photovoltaic array, a 2.25 MW electrolyzer, 450 kg of hydrogen storage, and a 1 MW fuel cell, and is evaluated using a 25-year hourly-resolution simulation framework. Economic performance is assessed through discounted cash-flow analysis, while environmental impacts are quantified using life-cycle assessment. Results demonstrate that integrating water reuse reduces the levelized cost of electricity from 0.10 to 0.0866 USD/kWh, avoids approximately 157,000 tonnes of CO₂-equivalent (tCO₂-eq)emissions, and enables the recovery of nearly 400,000 L/day of process water. By explicitly internalizing water-treatment capital and operating costs alongside water-savings benefits within the energy cost formulation, the study presents a generalizable framework linking hydrogen-based energy systems with circular water infrastructure, supporting industrial decarbonization and Sustainable Development Goals related to clean energy, responsible resource use, and climate action.